Conservation needs and opportunities drive LIFE funding allocation for European birds - Correia, Ricardo A.; Brommer, Jon E.; Haukka, Anna; Jonas, Leonie; Lehikoinen, Aleksi; Mammola, Stefano; Santangeli, Andrea (Elsevier BV, 2025)
Conservation resources are unevenly distributed among species and this can hamper conservation efforts. Previous research indicates that species popularity can be strongly associated with conservation funding allocation, suggesting conservation outcomes can be partly influenced by subjective human perceptions. We assessed the allocation of European Union LIFE projects targeting species conservation among European birds (548 species) and how it associates with species' conservation priorities, scientific knowledge availability, distribution, popularity and visual aesthetic attractiveness. We modelled how these factors relate to the probability that a species has received EU LIFE funding, and how many projects have targeted it. As expected given LIFE funding regulations, species listed in the EU Birds Directive Annex I are more likely to receive funding than non-listed species, and receive more projects. We also found that knowledge availability, presence in more EU member countries with access to LIFE funding, and higher conservation priority in Europe are positively associated with the probability of receiving funding, and the number of projects received. More popular species are less likely to receive conservation funding, but tend to receive more projects when allocated funding. Visual attractiveness was not associated with funding. These results suggest that pragmatic factors dominate funding allocation, but subjective factors still play a minor role. Our analysis also emphasises the need to consider non-funded species when assessing conservation funding allocation. Our findings underscore a need for targeted research on poorly-known species and opportunities for allocating conservation resources to underfunded species that need conservation action, are well-studied, and relatively popular.